2019
DOI: 10.3934/mbe.2019381
|View full text |Cite
|
Sign up to set email alerts
|

Parameter regions that give rise to $2 \lfloor \frac{n}{2}\rfloor +1$ positive steady states in the $n$-site phosphorylation system

Abstract: The distributive sequential n-site phosphorylation/dephosphorylation system is an important building block in networks of chemical reactions arising in molecular biology, which has been intensively studied. In the nice paper of Wang and Sontag (2008) it is shown that for certain choices of the reaction rate constants and total conservation constants, the system can have 2[ n 2 ] + 1 positive steady states (that is, n + 1 positive steady states for n even and n positive steady states for n odd). In this paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…For the two-site, distributive system studied here, in which we restricted attention to E tot = F tot , we found bistable points in H 4 at S tot /E tot = σ = 1.0078125, which suggests that the threshold lies at σ = 1, so that T(E tot , F tot ) = E tot when E tot = F tot . The conjecture above is consistent with recent work which showed that, when all enzymes follow the Michaelis-Menten reaction scheme, if S tot < E tot or S tot < F tot , parameter values can be found at which there are multiple steady-states but such multistationarity does not exist if S tot > E tot and S tot > F tot [58,89,90].…”
Section: Discussionsupporting
confidence: 90%
“…For the two-site, distributive system studied here, in which we restricted attention to E tot = F tot , we found bistable points in H 4 at S tot /E tot = σ = 1.0078125, which suggests that the threshold lies at σ = 1, so that T(E tot , F tot ) = E tot when E tot = F tot . The conjecture above is consistent with recent work which showed that, when all enzymes follow the Michaelis-Menten reaction scheme, if S tot < E tot or S tot < F tot , parameter values can be found at which there are multiple steady-states but such multistationarity does not exist if S tot > E tot and S tot > F tot [58,89,90].…”
Section: Discussionsupporting
confidence: 90%
“…We refer to [11] for a simple example and basic definitions, together with an explicit application to cascades with any number of layers. These degeneration tools are also applied to describe open regions where there are (or + 1) scpss for any in [12], where we also provide a basic systematic implementation in a computer algebra system.…”
Section: Some Recent Work On Biochemical Reaction Networkmentioning
confidence: 99%
“…[15,Lemma B.3]), as follows. We first found a vertex of the polytope whose corresponding coefficient is a positive polynomial (namely, the leading coefficient in (12)). Next, we chose a vector v in the interior of the corresponding cone in the polytope's outer normal fan.…”
Section: Multistationarity At All Processivity Levelsmentioning
confidence: 99%
“…Our results fit into related literature as follows. First, as other authors have done for their models of interest [5,12,18], we analyze simplified versions of the ERK network obtained by removing intermediate species and/or reactions (in some cases, bistability and oscillations can be "lifted" from smaller networks to larger ones [1,2,4,10,13]). Also, our proofs harness two results from previous work: a Hopf-bifurcation criterion for the reduced ERK network [15], and a criterion for multistationarity arising from degree theory [6,9].…”
Section: Introductionmentioning
confidence: 99%